Handbook of Antenna Technologies 2015
DOI: 10.1007/978-981-4560-75-7_86-1
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Sensors in Passive Wireless Sensing Systems

Abstract: Antenna sensors have received considerable interests in recent years due to their passive wireless operation, simple configuration, compact size, multiplexing capability, and multimodality sensitivity. Based on the principle of antenna backscattering, an antenna sensor can be wirelessly interrogated at middle range distances without an onboard battery. Since the antenna serves the dual function of sensing and communicating, an antenna sensor can be implemented with minimum number of components. As narrowband r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Moreover, a dual-resonant (TM01 and TM10 modes) microstrip antenna was proposed to detect the orientation of cracks and demonstrated that its sensivity was related to the relative permittivity and geometrical length [22]. Further information about TABS can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a dual-resonant (TM01 and TM10 modes) microstrip antenna was proposed to detect the orientation of cracks and demonstrated that its sensivity was related to the relative permittivity and geometrical length [22]. Further information about TABS can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
“…At any frequency, the quantity P t = (1− r ) mW, where r is the reflection coefficient calculated from the parameter S 11 (see Supporting Information) at that frequency. We define the “radiation efficiency” as η = G t / D , [ 19 ] where D is the directivity. The antenna is omnidirectional (we do not observe any significant directional dependence of the radiation) which is expected since the antenna dimension is much smaller than the wavelength [ 20 ] and hence the antenna approximates a point source that radiates equally in all directions (isotropic radiator).…”
Section: Resultsmentioning
confidence: 99%